Reducing alcohol use during pregnancy: Listening to women who drink as an intervention starting point - McBride, Nyanda; Carruthers, Susan; Hutchinson, D. (Sage Publications, 2012)
Objectives: This study assesses factors that contribute to alcohol consumption during pregnancy and identifies potential intervention strategies to reduce consumption. Methods: The study sample includes 142 pregnant women who attended a public hospital for prenatal health care in Perth, Western Australia. All participants returned a self-completion survey. Results: Women who discontinued drinking during pregnancy were significantly more likely to be engaged in full time home duties and had completed less formal education. Women who continued to drink were more likely to have drunk in previous pregnancies and during the preconception period. Nearly 40% of high risk women reported a negative comment in response to their drinking. One-third of women in the risky group were advised by a health professional not to drink alcohol. Women were most likely to drink in their own home or at the home of a friend. Conclusions: Participatory research with women who drink while pregnant can assist in identifying potential intervention strategies that have resonance with this group and therefore more potential for creating behaviour change. Implications: The World Health Organization recognises, and has done for over 10 years, that alcohol use during pregnancy which results in Foetal Alcohol Spectrum Disorder is the leading cause of environmental related birth defects and mental retardation in the Western world.